Knowledge Management in Higher Education Institutions: A Framework to Improve Collaboration - Mehta, Abhishek (Asian Review of Mechanical Engineering, 2021)
The reason for this paper is to introduce a system that increments information sharing and cooperation in Higher Education Institutions. The paper talks about the idea of information the board in advanced education establishments, introducing a systematization of information practices and apparatuses to connecting individuals (understudies, instructors, analysts, secretariat staff, outer elements) and advancing the information sharing across a few critical cycles and administrations in an advanced education organization, for example, the examination processes, growing experiences, understudy and graduated class administrations, managerial administrations and cycles, and key preparation and the executives. The structure purposed in this paper intends to further develop information practices and cycles which work with a climate and a culture of information cooperation, sharing and disclosure that ought to describe an establishment of advanced education.